2023
DOI: 10.1186/s12951-023-02045-4
|View full text |Cite
|
Sign up to set email alerts
|

Oral hydrogel nanoemulsion co-delivery system treats inflammatory bowel disease via anti-inflammatory and promoting intestinal mucosa repair

Fenting Lei,
Fancai Zeng,
Xin Yu
et al.

Abstract: Background Due to oral nano-delivery systems for the treatment of inflammatory bowel disease (IBD) are often failed to accumulated to the colonic site and could not achieve controlled drug release, it’s urgent to develop a microenvironment responsive drug delivery to improve therapy efficacy. Inflammation at the IBD site is mainly mediated by macrophages, which are the key effector cells. Excessive inflammation leads to oxidative stress and intestinal mucosal damage. The use of curcumin (CUR) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…The overabundance of ROS and the proinflammatory microenvironment could damage intestinal tissue and induce the destruction of crucial gut proteins and ultimately impair the integrity of the intestinal barrier. As the main junctions between epithelial cells of the intestinal mucosa, tight junctions are vital for the maintenance of intestinal homeostasis . We then investigated the epithelial barrier integrity by assessing the colonic expression levels of tight junctions ZO-1 and Occludin.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The overabundance of ROS and the proinflammatory microenvironment could damage intestinal tissue and induce the destruction of crucial gut proteins and ultimately impair the integrity of the intestinal barrier. As the main junctions between epithelial cells of the intestinal mucosa, tight junctions are vital for the maintenance of intestinal homeostasis . We then investigated the epithelial barrier integrity by assessing the colonic expression levels of tight junctions ZO-1 and Occludin.…”
Section: Resultsmentioning
confidence: 99%
“…As the main junctions between epithelial cells of the intestinal mucosa, tight junctions are vital for the maintenance of intestinal homeostasis. 37 We then investigated the epithelial barrier integrity by assessing the colonic expression levels of tight junctions ZO-1 and Occludin. As shown in Figure 7A−D, immunohistochemistry images revealed significantly reduced fluorescence in the DSS model group, indicating that the expression levels of ZO-1 and Occludin in the colon were significantly downregulated.…”
Section: Resistance Of Modified Ecn Against Gastrointestinal Assaultsmentioning
confidence: 99%
“…Three-dimensional molecular networks can also be administered to the patient through injections, which allow for precise delivery of the substance to the targeted area, such as the knee joint [43]. Another route is oral administration since hydrogels can effectively cope with the low pH of the stomach or even release the active substance in response to the acidic environment [44]. Biomaterials can also be delivered via ocular, nasal, vaginal, and rectal administration [45][46][47][48].…”
Section: Routes Of Administering Hydrogelsmentioning
confidence: 99%
“…Lei et al [75] prepared a Ph-responsive sodium alginate (SA) hydrogel-coated nanoemulsion that co-delivers CCM and emodin (EMO) CUR/EMO NE@SA, controls drug release in the colon, and specifically targets colonic macrophages. In preclinical studies, CUR/EMO NE@SA was shown to improve the inflammatory microenvironment of the colon by modulating inflammatory signaling and scavenging ROS from macrophages.…”
Section: Nanoemulsionmentioning
confidence: 99%